From Art to Agony: The Transformation of Aesthetic Ideals in The Ballad of Reading Gaol by Oscar Wilde - Kattel, Achut Raj; Dhakal, Anusiya (JODEM: Journal of Language and Literature, 2025)
Oscar Wilde’s life was very controversial in the Victorian period and he had to suffer a lot before death. The shift from aesthetics to suffering, pain, alienation, injustice and social hypocrisy attracts the researcher for the study of Wilde’s poem. The study inquires the major reason of Wilde’s transformation from subject of aestheticism to truth, the pain and suffering in life. The study aims to explore the change in his aesthetic thought by analyzing his ballad. For the purpose, theology and Christian doctrines explained by Joyce Sila Nduku, Father Patrick Boyle and Olivier Thomas Venard have been used. The major finding of the study is Wilde shifts from his theme of ‘art for art’s sake’ to the suffering, alienation and redemption of common people. The study concludes that Wilde understood social system and meaning of suffering after he lived in the prison. He suffered for salvation and redemption as suffering is for the good reason according to Christianity. The Ballad of Reading Gaol has the hope that the imprisoned murderer’s execution provides him religious redemption and peace though he missed social redemption. Social redemption is the love and care of people and possibility of rehabilitation. The prisoner’s execution in the ballad is very similar to Jesus Christ’s sacrifice for the redemption of all the sinners in the world.